Worlds together, worlds apart. Jeremy Adelman, Elizabeth Pollard, Robert Tignor. - Adelman, Jeremy; Pollard, Elizabeth (Elizabeth Ann); Tignor, Robert L. (W.W. Norton & Company, 2024)
Worlds Together, Worlds Apart has a global-by-design narrative which builds each chapter around big themes in world history that allow most of the regions to be discussed in each chapter while focusing updates on cutting-edge global topics that students care about, such as gender, the environment, migration, and technology.